2022
DOI: 10.17586/2220-8054-2022-13-6-593-607
|View full text |Cite
|
Sign up to set email alerts
|

Spin Boltzmann machine

Abstract: Boltzmann machine (BM) is a recurrent network, which has a wide range of applications in machine learning (ML) including dimensionality reduction, feature learning and classification. Standard BM is described by the Ising model and can be implemented as a spin ice based device. Such hardware implementation is faster and more energy efficient than a simulation on digital computers. At the moment, a hardware BM is a single purpose device designed on digital computers for a specific task. In the paper we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The optimization of the mean m is relatively simple and was already solved in [16]. Here we let m = 0 and focus on optimization of θ.…”
Section: Standard Deviation Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization of the mean m is relatively simple and was already solved in [16]. Here we let m = 0 and focus on optimization of θ.…”
Section: Standard Deviation Learningmentioning
confidence: 99%
“…Our initiative is to implement BM loss minimization as a relaxation in a magnetic device. In the article [16], we proposed an extended BM machine whose weights are included to degrees of freedom (DoF). We showed that the energy minimization of the system leads to memorization of the trained samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is not the electron charge but the electron spin that carries information [1]. The new wave of interest was inspired by the development of quantum computing and quantum computations (see, e.g., [2,3]). Correspondingly, one needs electronic devices which can distinguish the spin orientation and can control it.…”
Section: Introductionmentioning
confidence: 99%